1999
DOI: 10.1046/j.1365-2346.1999.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the laryngeal mask airway:factors affecting the incidence of post-operative adverse respiratory events in 300 patients

Abstract: The purpose of this study is to compare the incidence of undesirable respiratory events when the laryngeal mask airway is either removed from patients who are fully awake or from patients who are deeply anaesthetized. Three-hundred patients aged 1.5-81 years were randomly assigned to have their laryngeal mask airway removed either when deeply anaesthetized or after airway reflexes had returned. The occurrence of adverse respiratory events (coughing, oxygen desaturation and airway obstruction) was recorded. Air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Another seven trials were excluded since they were studies of adult patients. A total of 17 full-text randomized trials [ 7 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] were included in the final analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another seven trials were excluded since they were studies of adult patients. A total of 17 full-text randomized trials [ 7 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] were included in the final analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Baird, et al 3 reported that desaturation and airway obstruction following the LMA removal after full recovery occurred in 31% and 7% of adult patients, respectively. On the other hand, several previous studies on adults reported that the occurrence of such major complications was rare during LMA removal in the awake state.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of respiratory complications during LMA removal in awake patients has been reported as 48.7%. 3 A minimum sample size of 26 patients per group was required to achieve a power of 0.8 and an α value of 0.05 on the assumption that a 50% reduction of complications would be clinically significant. Statistical analysis was performed with SPSS 21.0 (IBM, Armonk, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 3 However, in a deep anesthetic state, suppression of airway reflexes may increase the incidence of aspiration and airway obstruction. 4 5 Therefore, providing an appropriate depth of anesthesia to achieve airway reflex suppression without delayed awakening is important for safe removal of a LMA.…”
Section: Introductionmentioning
confidence: 99%